2017
DOI: 10.1039/c7sc00880e
|View full text |Cite
|
Sign up to set email alerts
|

Near UV-Visible electronic absorption originating from charged amino acids in a monomeric protein

Abstract: We report 250–800 nm UV-Vis monomeric protein absorption originating from protein backbone–sidechain and sidechain–sidechain charge transfer transitions involving Lys/Glu residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(176 citation statements)
references
References 49 publications
(65 reference statements)
8
158
0
1
Order By: Relevance
“…Titration of Cu II into C‐peptide similarly resulted in an increased absorbance in the region at λ =280–300 nm, corresponding to a deprotonated backbone amide to Cu II charge transfer or interactions between charged side chains . Increased absorption at λ =600 nm was observed upon the addition of Cu II , which was consistent with a d–d transition at the Cu II center (Figure B).…”
Section: Figurementioning
confidence: 75%
See 1 more Smart Citation
“…Titration of Cu II into C‐peptide similarly resulted in an increased absorbance in the region at λ =280–300 nm, corresponding to a deprotonated backbone amide to Cu II charge transfer or interactions between charged side chains . Increased absorption at λ =600 nm was observed upon the addition of Cu II , which was consistent with a d–d transition at the Cu II center (Figure B).…”
Section: Figurementioning
confidence: 75%
“…Titration of Cr III show changes in the spectral profile relative to that of apo C‐peptide with increases in absorption at λ =260–300 nm (Figure A). Bands in this region may correspond to a weak d–d transition ( 4 A 2g → 4 T 1 (t 2 e 2 )); a strong carboxylate oxygen–metal charge transfer; interactions between charged groups, such as a glutamate side chain and the amino terminus; or a combination of the three; thus, the resulting spectral shifts may be attributed to either the introduction of a Cr III /C‐peptide complex or an electrostatic rearrangement between two charged amino acids in the sequence.…”
Section: Figurementioning
confidence: 99%
“…The nature of the optical properties is sensitive to the environment in which the glutamine molecules reside. It has previously been reported that charged amino acids already display an absorption in the range of 250-350 nm that is significantly red shifted (36, 37). The origins of the low energy absorption were attributed to charge transfer excitations.…”
Section: Resultsmentioning
confidence: 99%
“…Those amino acids having a strong (s; probability for non-specificity, Corr P < 10 −4 ) or moderate (m; Corr P < 10 −3 ) or weak (w; Corr P < 10 −2 ) association of their binding sites with their cognate codons/anticodons (Corr P = 1 implies no specificity; see table 1 of [44]) are also those that have the greatest number of characteristics relevant to increased photon dissipation, and therefore reproduction through the dissipation-replication relation, at the origin of life. The " * " indicates amino acids that absorb in the 260 nm window through charge transfer (CT) transitions [64]. and hydrophobic parts, that can adsorb to DNA or RNA and thereby keep them afloat at the surface would have been essential to photon dissipation.…”
Section: Accumulation Of Information Through the Dissipation-replicatmentioning
confidence: 99%
“…This is an 5-member aromatic heterocycle containing two nitrogen atoms and 3 carbon atoms known as an imidazole. Having two conjugate bonds, histidine absorbs strongly in the UVC (212 nm, = 5, 700) [76], however, it has a smaller absorption peak at 280 nm which has been attributed to photon-induced charge transfer (CT) transitions [64]. This could be important to the origin of life because imidazoles are known as amphoteric molecules, serving as both an acidic and alkaline (pKa = 14.5) catalyst for a very large number of important reactions in contemporary life, for example as a condensing agents for the phosphorylation of the nucleobases and the lipids.…”
Section: Catalysismentioning
confidence: 99%